Optimalisasi Dosis Kombinasi Asam Amino dan Glukosa Terlarut Terhadap Komposisi Kimia Tubuh Lobster Air Tawar - Mutmainnah, Nurul; Zulfiani,; Lidya,; Yunus, Yusdalifa Ekayanti; Yani, Fitri Indah; Sahabuddin,; Rusdi, Rismawaty (Journal Galung Tropika, 2025)
Freshwater lobster (Cherax quadricarinatus) is a fishery commodity with high economic value, and market demand continues to increase. However, one of the main challenges in cultivating freshwater lobsters is the low survival rate of fry, especially in the early stages of development. This research aims to optimize the dosage of a combination of amino acids and dissolved glucose to meet the nutritional needs of freshwater lobster fry and support their survival. This research was carried out at the Agriculture, Livestock, and Fisheries Greenhouse, Muhammadiyah University of Parepare, using freshwater lobster fry from captive breeding. The research method used was a Completely Randomized Design (CRD) with four treatment doses of a combination of amino acids and dissolved glucose, namely: A) 100 ppm glucose + 250 ppm amino acids, B) 150 ppm glucose + 200 ppm amino acids, C) 200 ppm glucose + 150 ppm amino acids, and D) 250 ppm glucose + 100 ppm amino acids, each with three replications. The parameters explained are the chemical composition of the body, including protein, fat, fiber, and BETN content. A combination dose of 250 ppm glucose and 100 ppm amino acids is most effective in improving the nutritional quality of freshwater lobsters (Cherax quadricarinatus). The results of this study show the highest protein content (14.28%), fat content (0.89%), and fiber content (0.7%), all of which are important for the growth and health of lobsters. Meanwhile, the combined dose of 100 ppm glucose + 250 ppm amino acids yielded the best BETN (4.95%). Overall, the 250-ppm glucose and 100 ppm amino acid combination is optimal for improving the chemical composition of the lobster's body.